Development and Bioavailability Assessment of Ramipril Nanoparticle Formulation - Pereira, Annie; Gadad, Anand Panchakshari; Patil, Archana Sidagouda; Dandagi, Panchakshari Mallappa (Indian Journal of Pharmaceutical Education and Research, 2019)
Ramipril, potent anti-hypertensive agent has been used in the treatment of hypertensive disorders. It has low bioavailability of 28-35% and short biological half-life (i.e. 2-4 hr). Thus this study attempts to evaluate chitosan-alginate nanoparticles as a novel drug delivery for Ramipril to sustain drug release and improve oral bioavailability. Nanoparticles were prepared by ionotropic pre-gelation technique using chitosan and sodium alginate polymers. Total nine formulations (F1 to F9) were prepared by varying the polymer concentrations. The nanoparticles were characterized for particle size, drug content, drug entrapment efficiency, zeta potential, surface morphology (TEM), percentage yield, in-vitro diffusion study, in-vivo bioavailability studies and stability studies. All prepared formulations were in the nanosize range of 190.5±6.15nm to 361.76±3.32 and with spherical morphology. The drug content and entrapment efficiency was found to maximum for F5 formulation, percentage yield was in the range of 53.72±2.04 to 77.91±0.565% which mainly depends upon polymer concentration. The zeta potential of optimised formulation F5 was found to be -34.2mV, showed good stability of nanoparticles during storage. The in-vitro drug release profile showed the suitability of nanoparticles for pH dependent and sustained release of Ramipril for prolonged time. Kinetic modelling revealed that the in-vitro drug release followed peppas model and non-fickian diffusion. From the in vivo studies it was predicted that oral bioavailability of Ramipril nanoparticles improved 2.17 times more than the pure drug. Stability studies carried out for optimized formulation F5 showed that the nanoparticles are more stable at 5±3°C.
Keywords: Ramipril; Chitosan; Sodium alginate; Ionotropic pre-gelation technique; Chitosan-alginate polymeric complex; pH sensitive; Oral bioavailability